Etnografi Garna Tentang Kebudayaan Baduy (Catatan untuk Mengenang Prof H. Judistira K. Garna, Ph.D) - Ade Makmur Kartawinata (Umbara, 2020)
This article explains the way Judistira K Garna describing Baduy culture. His ethnographic work is about the life of the Baduy people and their response to changes from the perspective of the Baduy themselves. Koentjaraningrat referred Judistira's work as "Ethnography of Garna" which resulted from a functional interpretation of Baduy culture. Garna’s work  explains things that are not in terms of tools to control their life order, but are sources for understanding them. The values of their life we often do, we also seek, as far as possible, should be accommodated in the flow of their life. If the expected results of socio-cultural change are achieved in Baduy, both in the form of social institutions and new procedures, it will not only be the work of outsiders but also the result of their willingness and efforts to accept.